Evaluation of Bone Metastasis from Hepatocellular Carcinoma Using (18)F-FDG PET/CT and (99m)Tc-HDP Bone Scintigraphy: Characteristics of Soft Tissue Formation - Seo, Hyo Jung (Springer-Verlag, 2011)
PURPOSE: Bone metastasis from hepatocellular carcinoma (HCC) can present with soft tissue formation, resulting in oncologic emergency. Contrast-enhanced FDG PET/CT and bone scintigraphy were compared to evaluate characteristics of bone metastases with or without soft tissue formation from HCC. METHODS: Of 4,151 patients with HCC, 263 patients had bone metastases. Eighty-five patients with bone metastasis from HCC underwent contrast-enhanced FDG PET/CT. Fifty-four of the enrolled subjects had recent (99m)Tc-HDP bone scintigraphy available for comparison. Metastatic bone lesions were identified with visual inspection on FDG PET/CT, and maximum standardized uptake value (SUV(max)) was used for the quantitative analysis. Confirmation of bone metastasis was based on histopathology, combined imaging modalities, or serial follow-up studies. RESULTS: Forty-seven patients (55%) presented with soft tissue formation, while the remaining 38 patients presented without soft tissue formation. Frequent sites of bone metastases from HCC were the spine (39%), pelvis (19%), and rib cage (14%). The soft-tissue-formation group had more frequent bone pain (77 vs. 37%, p < 0.0001), higher SUV(max) (6.02 vs. 3.52, p < 0.007), and higher incidence of photon defect in bone scintigraphy (75 vs. 0%) compared to the non-soft-tissue-formation group. FDG PET/CT had higher detection rate for bone metastasis than bone scintigraphy both in lesion-based analysis (98 vs. 53%, p = 0.0015) and in patient-based analysis (100 vs. 80%, p < 0 .001). CONCLUSIONS: Bone metastasis from HCC showed a high incidence of soft tissue formation requiring emergency treatment. Although the characteristic findings for soft tissue formation such as photon defect in bone scintigraphy are helpful in detection, overall detectability of bone metastasis is higher in FDG PET/CT. Contrast-enhanced PET/CT will be useful in finding and delineating soft-tissue-forming bone metastasis from HCC.